Ергазіофіти київської міської агломерації - Yavorska, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
Summarized floristic data of the species escaped from cultivation in Kyiv and adjacent areas are given. The approaches to the analysis of this group of species in the adventive flora are presented. The periods of this group formation is given in historical aspect. The results of investigations on species distribution, systematic, biological-morphological and geographical structure of ergasiophytes and xenoergaziophytes are cited. These species naturalization in Kyiv region is analyzed.